Retinoic acid treatment recruits macrophages and increases axonal regeneration after optic nerve injury in the frog Rana pipiens - Valeria De La Rosa-Reyes (Public Library of Science (PLoS), 2021)
Retinoic acid (RA) plays major roles during nervous system development, and during regeneration of the adult nervous system. We have previously shown that components of the RA signaling pathway are upregulated after optic nerve injury, and that exogenous application of all-trans retinoic acid (ATRA) greatly increases the survival of axotomized retinal ganglion cells (RGCs). The objective of the present study is to investigate the effects of ATRA application on the macrophages in the optic nerve after injury, and to determine whether this affects axonal regeneration. The optic nerve was crushed and treated with PBS, ATRA and/or clodronate-loaded liposomes. Nerves were examined at one and two weeks after axotomy with light microscopy, immunocytochemistry and electron microscopy. ATRA application to the optic nerve caused transient increases in the number of macrophages and microglia one week after injury. The macrophages are consistently labeled with M2-type markers, and have considerable phagocytic activity. ATRA increased ultrastructural features of ongoing phagocytic activity in macrophages at one and two weeks. ATRA treatment also significantly increased the numbers of regenerating GAP-43-labeled axons. Clodronate liposome treatment depleted macrophage numbers by 80%, completely eliminated the ATRA-mediated increase in axonal regeneration, and clodronate treatment alone decreased axonal numbers by 30%. These results suggest that the success of axon regeneration is partially dependent on the presence of debris-phagocytosing macrophages, and that the increases in regeneration caused by ATRA are in part due to their increased numbers. Further studies will examine whether macrophage depletion affects RGC survival.